QUALITY AND CHEMISTRY OF AFRICAN BIRDS EYE CHILI (CAPSICUM FRUTESCENS) FROM ZAMBIA - Juliani, H. R.; Coppin, J.; Kim, K.; Malumo, H.; Diawuo, B.; Langenhoven, P.; Simon, J. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
African Birds Eye Chili (Capsicum frutescens) is a specialty hot pepper of increasing interest to consumers and to those who enjoy and rely on hot peppers. Assessing of the chemistry and quality of this spice is becoming increasingly important to increase its market access and better define the product variation from different producing regions. The objective of this study is to assess the chemistry and quality of African Birds Eye Chili grown in Zambia. Fruit samples from this plant were grown and harvested (2006-2007 seasons) from the Chinyanja Triangle area and from the 2008 season from Chongwe, Kalomo and Mpongwe and subjected to proximate and chemical analysis. The deep orange color of the Zambian African Birds Eye Chili was found to be very positive. All the samples showed low levels of moisture (<10%) indicating proper drying and showed no contamination with sand. The samples from Chongwe and Mpongwe showed the highest levels of capsaicinoids (by HPLC), with capsaicin levels of >1%, and 1%, respectively; and dihydrocapsaicin reaching 0.5-0.7% and 0.5%, respectively from these sites. Samples from the Chinyanja Triangle, 2006-07 were found to be lower (0.6-0.8% capsaicin, 0.3-0.5% dihydrocapsaicin) but direct comparisons are not possible as those studies were conducted in an earlier growing season. In 2008 season, the application of Good Agricultural Practices, higher quality seeds and improved production practices (improved weeding and drying) which appeared to result in the production of high quality Chili. A study to compare Zambian African Birds Eye Chili to other hot pepper commercial samples found on the USA market found that the Zambian product contained far higher levels of capsaicin and were of superior quality to the commercial hot pepper products.